TEACHING ARABIC LANGUAGE SKILLS THROUGH LANGUAGE GAMES - LP Nurjannah; Esther Heronica; Andre Setiawan (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Arabic language teaching encompasses the acquisition of four language skills: listening (al-istima’), speaking (al-kalam), reading (al-qira’ah), and writing (al-kitabah). Mastering these four language skills requires considerable time and effort. The stigma surrounding the difficulty of teaching Arabic is still significant, hence the need for educators to employ creativity in delivering engaging Arabic language instruction. Language games can be one of the options as a method for teaching Arabic language. Arabic language instruction packaged with language games can create an impression that teaching is easy and interesting, thus avoiding monotony. This study aims to provide examples of several language games that can be applied in Arabic language instruction while assessing the benefits of implementing these games. The research adopts a literature review approach with qualitative descriptive analysis. Data sources include relevant books, journals, articles, and papers. Data collection is conducted through documentation techniques and analyzed using content analysis methods. The research findings indicate that language games applied in Arabic language instruction are an effective solution for mastering the four language skills with maximal student involvement. The teaching atmosphere becomes enjoyable, fostering students' confidence.